2018
DOI: 10.1126/science.aas8806
|View full text |Cite
|
Sign up to set email alerts
|

Human influence on the seasonal cycle of tropospheric temperature

Abstract: We provide scientific evidence that a human-caused signal in the seasonal cycle of tropospheric temperature has emerged from the background noise of natural variability. Satellite data and the anthropogenic "fingerprint" predicted by climate models show common large-scale changes in geographical patterns of seasonal cycle amplitude. These common features include increases in amplitude at mid-latitudes in both hemispheres, amplitude decreases at high latitudes in the Southern Hemisphere, and small changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 118 publications
9
112
1
Order By: Relevance
“…Second, at the lowest frequencies, model spectral densities are higher than in NCEP-2 and ERA-I, and the 95 % posterior intervals of nearly all of the simulated spectra do not overlap with the reanalysis spectra. This difference in the amplitude of simulated and observed variability (which is most pronounced in the tropics) is consistent with findings obtained elsewhere for multi-model analyses of tropospheric temperature (Santer et al, 2018). A model bias in the opposite direction to that found here (i.e., a systematic underestimate of the amplitude of observed internal variability on multidecadal timescales) would be more concerning -such an error would spuriously inflate signal-to-noise ratios for anthropogenic signal detection (Santer et al, 2018).…”
Section: Results From the 30-year Assessment Of Large-scale Temperaturesupporting
confidence: 90%
See 3 more Smart Citations
“…Second, at the lowest frequencies, model spectral densities are higher than in NCEP-2 and ERA-I, and the 95 % posterior intervals of nearly all of the simulated spectra do not overlap with the reanalysis spectra. This difference in the amplitude of simulated and observed variability (which is most pronounced in the tropics) is consistent with findings obtained elsewhere for multi-model analyses of tropospheric temperature (Santer et al, 2018). A model bias in the opposite direction to that found here (i.e., a systematic underestimate of the amplitude of observed internal variability on multidecadal timescales) would be more concerning -such an error would spuriously inflate signal-to-noise ratios for anthropogenic signal detection (Santer et al, 2018).…”
Section: Results From the 30-year Assessment Of Large-scale Temperaturesupporting
confidence: 90%
“…This choice makes the DLM seasonal component analogous to calculating a constant climatology, which is a common practice in climate science. If small changes in the seasonal amplitudes exist (Santer et al, 2018) the changes are aliased in the DLM residuals, although we found no evidence of this in the data.…”
Section: Specification Of the Evolution Variancecontrasting
confidence: 68%
See 2 more Smart Citations
“…The last box plot in (D) shows the IPCC AR5 likely (>66% probability; equivalent to 17 to 83% range) range. Each box plot shows 5 to 95% range, likely range, and median value, as illustrated in the legend.onMarch 20, 2020 http://advances.sciencemag.org/ Downloaded from model's 1981-2014 regional trend map based only on pattern covariance, similar to standard detection and attribution methods(34), and is independent of any global mean warming trends.This approach of "fingerprint of spatial trend variation" yields a correlation of each model's pattern covariance with TCR (R = 0.59 inFig. 4B, compared with R = 0.64 for the correlation of TCR with recent global mean warming inFig.…”
mentioning
confidence: 99%